Problems of philosophy;: an introductory survey - Cunningham, Gustavus Watts (H. Holt & Co., 1924)
Introduction: philosophy and life -- Common sense and science -- The method of science -- Classification of the sciences -- Philosophy and the sciences -- The intellectual enterprise: its nature -- The intellectual enterprise: characteristics of judgement -- The intellectual enterprise: its certainty -- The assumption of intelligence: causality -- Matter: historical survey -- Matter: appearances and reality -- Space and time -- Evolution: its meaning and types -- Evolution: its implications -- Mind: historical survey -- Mind: critical estimate of views -- Mind and body -- The society of minds -- Freedom of thought -- Problem of sovreignity -- The world of values -- Problems of aesthetic values -- The nature of goodness -- Creation of goodness: The problem of freedom -- Ultimate significance of goodness: belief in God -- Ultimate significance of goodness: belief in God (Cont.) -- Conservation of goodness: belief in immortality.